Komunikasi Kepemimpinan Dalam Menjaga Kinerja Pegawai Dinas Komunikasi Informatika Dan Statistik Nusa Tenggara Barat - Atus Leslessy; Joko Prayitno; Ni Putu Sasmika Dewi (PT. Gauri Narendra Patraka, 2023)
This research is directed to get a description of Leadership Communication in Maintaining Employee The objectives of this study are: (1) to describe the forms of leadership communication in maintaining employee performance, (2) to identify the inhibiting factors of leadership communication in maintaining employee performance, (3) to analyze the implications of leadership communication in maintaining employee performance. This study uses interpersonal communication theory. The method used in this study is a qualitative method. The data sources used are primary data sources and secondary data sources. Data collection techniques used are observation, interviews, and documentation. The data obtained and then analyzed through three stages, namely data reduction, display or data presentation, data verification or data collection. The results of the study can be concluded as follows: 1) the communication used in maintaining employee performance is internal communication and the communication used is verbal communication which can be conveyed via the Whatsapp group and if the message conveyed to employees is not understood then the leadership holds a meeting to discuss in more detail so that it can be understood 2) There are many inhibiting factors experienced such as computers, cameras (canon, air conditioner, wifi, and a lack of makeshift equipment workforce. 3)